Soil Moisture Control and Monitoring System Prototype Using the Internet of Things Network Based on Arduino Via Telegram Application - Daryl Saputra (Komunitas Dosen Indonesia, 2021)
The purpose of this research is to find out and get adequate information about soil moisture so that it can be utilized and maximized, especially in terms of farming so that it can help to suppress the effects of global environmental warming in this era of globalization and increasingly modern technology. The object of this research is the measurement of soil moisture which can be seen through the control and monitoring system prototype using the internet of things (IOT) network based on Arduino via the telegram application using props. The findings of this study can be concluded as follows; First, soil moisture can be found through the Arduino-based network using the telegram application. Second, with the ease of technology like this, it will greatly facilitate the lives of many people, especially in terms of farming so that they can better know the soil moisture content and the process of watering plants regularly every day. Third, with the ease of technology in terms of farming, it can help to minimize the effects of global warming on the growing environment.